2000
DOI: 10.1080/15298660008984516
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cost-Effectiveness of Various Passive Monitors and Active Monitors for Industrial Hygiene Sampling

Abstract: A framework for evaluating passive or active industrial hygiene air sampling monitors on a cost-effectiveness basis is described. Five passive monitors and one active monitor (charcoal tube with pump) were compared in several hypothetical scenarios. Using certain assumptions regarding method validation costs, sampling equipment costs, and labor costs, both a per sample cost and a total annual cost were calculated for each type of sampling monitor as a function of total samples taken per year. The results of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The measurements are time consuming and accompanied by considerable labour costs. Passive sampling may be an alternative as it is simple, cost-effective and less intrusive ( Nothstein et al , 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…The measurements are time consuming and accompanied by considerable labour costs. Passive sampling may be an alternative as it is simple, cost-effective and less intrusive ( Nothstein et al , 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…The simplicity of measurement devices allowed for accurate measurements being obtainable from unsupervised workers with minimal or no training (Liljelind et al, 2000(Liljelind et al, , 2001Egeghy et al, 2002;Sunnesson et al, 2002;Eriksson et al, 2005). Hence, results have been promising and SAE may be seen as cost-effective means of obtaining large datasets (Nothstein et al, 2000). However, it is unclear whether SAE also provides insight into long-term exposure, since Sunnesson et al (2002) observed that enthusiasm of participants sometimes decreased after the first couple of measurement sessions.…”
Section: Introductionmentioning
confidence: 99%
“…Passive samplers are substantially less costly to construct and deploy than typical central monitoring equipment because they do not require a pump, flow control equipment, or a power source (Krupa and Legge 2000;Nothstein et al 2000). Briggs et al (2000) used passive samplers to measure nitrogen dioxide at 80 sites in four metropolitan areas to develop an air quality model.…”
Section: Introductionmentioning
confidence: 99%